Analisis Data Training Karyawan Menggunakan Power BI Software as a Service di Main Dealer Honda Sumatera Utara - Nazrica, Sherly Ani; Putra, Hardiansyah; Khaliq, Abdul (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This research analyzes and visualizes employee training data at Main Dealer Honda North Sumatra using Power BI SaaS. The study utilized 4,706 data points from 2024, encompassing training status (Trained & Untrained), position, tenure, and employee generation. The methodology involved data collection, transformation, and the creation of an interactive Power BI dashboard. This dashboard facilitates monitoring employee training progress via filters based on dealer, employee name, or position, enabling more efficient data-driven decision-making. Results show Power BI SaaS significantly improves training data management efficiency, program effectiveness evaluation, and human resource development strategy refinement. The interactive dashboard provides real-time insights into training participation rates, identifying untrained employees and enabling targeted training initiatives. The research contributes to the literature on Power BI applications in employee training management and offers practical implications for improving HR strategies within the automotive sector. The findings highlight the benefits of utilizing analytical technology for effective employee training management and data-driven decision-making.